2022
DOI: 10.1044/2021_lshss-20-00148
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities to Enhance Children's Communication Development at School in Underserved Communities

Abstract: Purpose: Alternative service delivery approaches are required to provide support for children with communication difficulties in underserved communities. Schools have a unique set of assets that can be utilized to provide this support. This study explored what the education sector and classrooms in the early years of schooling offer as support for children with communication difficulties in an underserved Majority World country, the Maldives. The objective was to identify opportunities to enhance s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…21,42 In addition, it has been widely reported that the lack of qualified professionals to identify and provide quality communication services in schools is one of the major barriers for students to advance in their educational process. [47][48][49][50] Similarly, speech-language therapy has a positive impact on inclusive education as it contributes to the adaptation or flexibilization of the curriculum, the formulation and implementation of augmentative and alternative communication systems, counseling for parents, advice for teachers and the approach to the communication skills of both students with disabilities and other students. This includes students who are not contemplated in Decree 1421 of 2017 6 or in Law 2216 of 2022, 7 such as people with exceptional abilities and talents.…”
Section: An Identity Problemmentioning
confidence: 99%
“…21,42 In addition, it has been widely reported that the lack of qualified professionals to identify and provide quality communication services in schools is one of the major barriers for students to advance in their educational process. [47][48][49][50] Similarly, speech-language therapy has a positive impact on inclusive education as it contributes to the adaptation or flexibilization of the curriculum, the formulation and implementation of augmentative and alternative communication systems, counseling for parents, advice for teachers and the approach to the communication skills of both students with disabilities and other students. This includes students who are not contemplated in Decree 1421 of 2017 6 or in Law 2216 of 2022, 7 such as people with exceptional abilities and talents.…”
Section: An Identity Problemmentioning
confidence: 99%